Utilization of Digital Literacy in Islamic Religious Education Learning to Improve Students’ Critical Thinking Skills in the 21st Century at Madrasah Ibtidaiyah 1 Pasaman Barat - Farina, Dahlia (Program Pascasarjana UMSB, 2025)
One of the paradigm shifts in Islamic Religious Education is that it refers to a learning approach that still applies conventional education. So learning is still considered classical, there is a lack of technological progress in learning, and the teaching staff is low. This research was motivated by the low critical thinking skills of class XII students at MIN 1 Pasaman. The aim of this research is to find out how teachers' strategies in the 21st century improve students' critical thinking skills in PAI learning through digital literacy. This research is qualitative research with the type of research used, namely through participant observation, in-depth interviews, and documentation. The results of the research show that the strategies implemented by class implementation of learning, and evaluation of learning. One of the teacher's strategies through digital literacy is that teachers use laptops, projectors, internet networks, modules, and E-learning in PAI learning